Choanotaenia intestinalis sp.Nov. (Cestoda: Dilepididae) from Venellus indicus - Bhure1, S.S. Nanware1*, R.M. Dhondge2 and D.B. (Recent Research in Science and Technology, 2011)
The present communication deals with a new species of the genus Choanotaenia, [1] from the intestine of Venellus indicus at Kinwat, Disrict Nanded. (M.S.), India. The new species Choanotaenia intestinalis Sp. Nov. is characterized by having scolex medium, globular to oval in shape, suckers four, oval to rounded, overlapping each other, rostellum armed having 10-12 hooks in a single circle, neck short, mature segment longer than broad, somewhat squarish in shape, testes oval to rounded, 14 in numbers, mostly post-ovarian, cirrus pouch elongated, placed 1/3 rd from anterior margin of the segment, cirrus small, tube like, within the cirrus pouch, genital pore marginal, unilateral, vagina posterior to cirrus pouch, ovary dumbel shaped, gravid segment broader than long, egg capsules 50-60 in numbers, having single egg in each egg capsule.